Case Report and Review of Literature: Familial Malignant Pleural Mesothelioma in a 39 Years Old Patient With an Inconclusive 18F-FDG PET/CT Result - Idkedek, Mayar; Tahayneh, Kareem S.; Abu-Akar, Firas; Bakri, Izzeddin A. (Frontiers in Surgery, 2022)
Malignant pleural mesothelioma (MPM) is a rare yet aggressive neoplasm that was linked only to asbestos exposure for decades, although familial clusters were diagnosed with MPM without a known history of asbestos exposure most likely due to genetic susceptibility. Here, we describe a case of familial malignant mesothelioma in a 39 years old patient with a confirmed BAP1 mutation in addition to a known family history with the same mutation. The patient presented with progressive shortness of breath and recurrent pleural effusions and diagnosis was made through biopsies taken during uniportal Video-Assisted Thoracoscopic Surgery. After the inconclusive result of 18F-FDG PET/CT scan, subxiphoid uniportal Video-Assisted Thoracoscopic Surgery left pleural and laparoscopic peritoneal biopsies were obtained for staging and evaluating contralateral lung and peritoneal cavity. Finally, two important educational values should be acquired from this case: genetic predisposition and BAP1 tumor suppressor gene mutation might affect the age of presentation and overall prognosis of the disease. Also, 18F-FDG PET/CT scan may not be the best modality for staging and confirming the diagnosis of malignant pleural mesothelioma.